THE STUDY OF PHYSICAL CHARACTERISTICS OF GRANULAR ORGANIC FERTILIZER WITH TWO ADHESIVES - Utari, Ni Wayan Arya (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Granular organic fertilizer is a fertilizer that is partially or completely derived fromorganicmaterials in the formof dense granules. The objectives of this research were to evaluate the effect of adhesives materials and theircompositions on the physical characteristics of granular organic fertilizer produced. This researchwas conductedat the Bioprocess and Post Harvest Engineering Laboratory and also atPower and Agricultural MachineryLaboratory, Department of Agricultural Engineering, Lampung University. The design of this study usedRandomized Complete Block (RCB)with factorial arrangementand three replications. The first factor consistedof two levels : clay and starch. The second factorwere the percentage of the adhesivesmaterials : 5%, 8%, 11%.Each experimental unitweighted 4 kg rawmaterials of the organic fertilizer.The results showed that11%of clayis themost optimal adhesive formaking granular organic fertilizers. Higher percentage of adhesivesmaterialstended to increase bulk density, durability,water absorption, and dispersiontime of the granular organic fertilizer.However, statisticallythe type of adhesivesmaterials and their compositionhad significant effect onlyonpercentageof granule size for 2-5 mm and dispersion time.